Speech Acts in Learning Indonesian Language - Mochamad Noor Hidayat (Journal of linguistics, culture and communication, 2023)
This study aims to identify the types and forms of speech acts teachers and students use in learning Indonesian in class VII B of (x) junior high school. This research has a qualitative approach and uses a descriptive method. In data collection activities, researchers act as the primary data collection instrument. The results of this study show that the speech acts of teachers and students during the learning process take place there are locutionary, illocutionary, and perlocutionary speech acts used by teachers and students. In addition, teacher and student utterances also have various functions, such as declarative, representative or assertive, directive, expressive, and commissive. The forms of speech teachers and students use during the learning process are direct and indirect. The implications of this research as additional data in communicating between teachers and students in the learning process and data collection activities, researchers act as the main instrument of data collection.